Badi’s eloquence in Gibran’s literature - جعلوك مضر; تيسير جريكوس; وفاء جمعة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The creative image is an important means that the poet uses to express the secrets and turmoil of his soul, and one of the most prominent techniques by which the writer expresses what is turbulent within himself, by revealing its components with subtle, powerful expressions that make him swim with his imagination, mind, and heart. Literature, in its two types, poetry and prose, is speech that its owner chooses based on its goal and basic function, which is to influence and draw the attention of the recipient in the first place. Hence, it was necessary for the word to include aesthetic values ​​that help the poet reach his goal, and perhaps creative effects are one of the means to achieve his goal.